Enoch, Levi and Jubilees on Sexuality. Attitudes towards sexuality in the early Enoch literature, the Aramaic Levi Document, and the Book of Jubilees, William Loader : book review - Venter, P. M. (Old Testament essays, 2009)
This publication investigates mental attitudes towards sexuality in the pseudepigraphical books of 1 Enoch, the fragmented Aramaic Levi and Jubilees. It is the first of a larger project exploring attitudes towards what Loader calls the "central aspect of our common humanity" (p. 313) in Judaism and Christianity of the Hellenistic Greco-Roman era (3rd century B.C.E. - 1st century C.E.). The three books examined here are representing the earliest and most influential works of this era.